Extraction of phytochemicals from pericarpium citri reticulatae and spica prunella - Loh Jia, Liang (Universiti Sains Malaysia, 2009)
Pericarpium Citri reticulatae and Spica prune/la are two herbs commonly used in Traditional Chinese Medicine concoctions. In this study, a Soxhlet method for the extraction of phytochemicals from Pericarpium Citri reticulatae and Spica prunella using methanol, n-hexane and distilled water is described. Then-hexane extract yield was very high as compared to the other solvents. Preliminary screening of different Classes of phytochemicals in the extracts gave adequate information that was supported by using other sophisticated analytical techniques. It has been observed that the extraction at larger scale be preferred to get sufficient yield and consequently a large number of components into the extracts. The distilled water extract of Pericarpium Citri reticulatae contains saponins and possibly flavonoids; the distilled water extract of Spica prunella contains saponins; and the methanol extract of Spica prunella contains free acids and possibly flavonoids and tannins.